Comparative analysis on the immunoregulatory roles of ferritin M in hybrid fish (Carassius cuvieri ♀ × Carassius auratus red var ♂) and its parental species after bacterial infection. Issue 126 (July 2022) - Xiong, Ning-Xia; Huang, Jin-Fang; Li, Ke-Xin; Li, Shi-Yun; Zhao, Jia-Hui; Wang, Rou; Ou, Jie; Fan, Lan-Fen; Luo, Sheng-Wei; Liu, Shao-Jun
Abstract: Ferritin M is involved in the regulation of fish immunity. In this study, open reading frame (ORF) sequences of ferritin M from hybrid fish and its parental species were 534 bp. Tissue-specific analysis indicated that the highest level of ferritin M from red crucian carp was observed in kidney, while peaked expressions of ferritin M from white crucian carp and hybrid carp were observed in gill. Elevated levels of ferritin M from hybrid carp and its parental species were detected in immune-related tissues following Aeromonas hydrophila infection or in cultured fish cell lines after lipopolysaccharide (LPS) challenge. Ferritin M overexpression could attenuate NF-κB and TNFα promoter activity in their respective fish cells. Purified ferritin M fusion proteins elicited in vitro binding activity to A. hydrophila and Edwardsiella tarda, lowered bacterial dissemination to tissues and alleviated inflammatory response. Furthermore, treatment with ferritin M fusion proteins could mitigate bacteria-induced liver damage and rescue antioxidant activity. These results suggested that ferritin M in hybrid fish showed a similar immune defense against bacteria infection in comparison with those of its parental species. Highlights: Structure of ferritin M in hybrid crucian carp was compared with those of its parents. Up-regulated expressions of ferritin M were observed following A. hydrophila challenge and LPS stimulation. Ferritin M could show the binding activity to A. hydrophila and E. tarda.